Theobroma cacao L. pathogenesis-related gene tandem array members show diverse expression dynamics in response to pathogen colonization. (December 2016) - Fister, Andrew; Mejia, Luis; Zhang, Yufan; Herre, Edward; Maximova, Siela; Guiltinan, Mark
Abstract Background The pathogenesis-related (PR) group of proteins are operationally defined as polypeptides that increase in concentration in plant tissues upon contact with a pathogen. To date, 17 classes of highly divergent proteins have been described that act through multiple mechanisms of pathogen resistance. Characterizing these families in cacao, an economically important tree crop, and comparing the families to those in other species, is an important step in understanding cacao's immune response. Results Using publically available resources, all members of the 17 recognized pathogenesis-related gene families in the genome ofTheobroma cacao were identified and annotated resulting in a set of 350 members in both published cacao genomes. Approximately 50 % of these genes are organized in tandem arrays scattered throughout the genome. This feature was observed in five additional plant taxa (three dicots and two monocots), suggesting that tandem duplication has played an important role in the evolution of the PR genes in higher plants. Expression profiling captured the dynamics and complexity of PR genes expression at basal levels and after induction by two cacao pathogens (the oomycete, Phytophthora palmivora, and the fungus, Colletotrichum theobromicola ), identifying specific genes within families that are more responsive to pathogen challenge. Subsequent qRT-PCR validated the induction of several PR-1, PR-3, PR-4, and PR-10 family members, with greater than 1000 fold induction detected for specific genes. Conclusions We describe candidate genes that are likely to be involved in cacao's defense againstPhytophthora andColletotrichum infection and could be potentially useful for marker-assisted selection for breeding of disease resistant cacao varieties. The data presented here, along with existing cacao—omics resources, will enable targeted functional genetic screening of defense genes likely to play critical functions in cacao's defense against its pathogens.